Regulatory T cells in erythema nodosum leprosum maintain anti-inflammatory function - Negera, Edessa; Bobosha, Kidist; Aseffa, Abraham; Dockrell, Hazel M.; Lockwood, Diana N. J.; Walker, Stephen L. (PLoS neglected tropical diseases, 2022)
The numbers of circulating regulatory T cells (Tregs) are increased in lepromatous leprosy (LL) but reduced in erythema nodosum leprosum (ENL), the inflammatory complication of LL. It is unclear whether the suppressive function of Tregs is intact in both these conditions. A longitudinal study recruited participants at ALERT Hospital, Ethiopia. Peripheral blood samples were obtained before and after 24 weeks of prednisolone treatment for ENL and multidrug therapy (MDT) for participants with LL. We evaluated the suppressive function of Tregs in the peripheral blood mononuclear cells (PBMCs) of participants with LL and ENL by analysis of TNFα, IFNγ and IL-10 responses to Mycobacterium leprae (M. leprae) stimulation before and after depletion of CD25+ cells. 30 LL participants with ENL and 30 LL participants without ENL were recruited. The depletion of CD25+ cells from PBMCs was associated with enhanced TNFα and IFNγ responses to M. leprae stimulation before and after 24 weeks treatment of LL with MDT and of ENL with prednisolone. The addition of autologous CD25+ cells to CD25+ depleted PBMCs abolished these responses. In both non-reactional LL and ENL groups mitogen (PHA)-induced TNFα and IFNγ responses were not affected by depletion of CD25+ cells either before or after treatment. Depleting CD25+ cells did not affect the IL-10 response to M. leprae before and after 24 weeks of MDT in participants with LL. However, depletion of CD25+ cells was associated with an enhanced IL-10 response on stimulation with M. leprae in untreated participants with ENL and reduced IL-10 responses in treated individuals with ENL. The enhanced IL-10 in untreated ENL and the reduced IL-10 response in prednisolone treated individuals with ENL was abolished by addition of autologous CD25+ cells. The findings support the hypothesis that the impaired cell-mediated immune response in individuals with LL is M. leprae antigen specific and the unresponsiveness can be reversed by depleting CD25+ cells. Our results suggest that the suppressive function of Tregs in ENL is intact despite ENL being associated with reduced numbers of Tregs. The lack of difference in IL-10 response in control PBMCs and CD25+ depleted PBMCs in individuals with LL and the increased IL-10 response following the depletion of CD25+ cells in individuals with untreated ENL suggest that the mechanism of immune regulation by Tregs in leprosy appears independent of IL-10 or that other cells may be responsible for IL-10 production in leprosy. The present findings highlight mechanisms of T cell regulation in LL and ENL and provide insights into the control of peripheral immune tolerance, identifying Tregs as a potential therapeutic target.